Correlation and risk factor analysis of suicidal behavior in adolescents with depression: the impact of stress and childhood trauma - Dai, Lilei; Du, Hui; Zhao, Dan; Shu, Jing; He, Xinfu (Frontiers in Psychiatry, 2025)
ObjectiveThis study investigates the correlation between suicidal behavior and various stress factors in a sample of hospitalized adolescents with depression.MethodsA cross-sectional survey was conducted on 254 adolescent patients with depression from Aug 2022 to May 2024. Participants were assessed using PHQ-11, CTQ-SF, and SSMSS.ResultsThe suicide group (150 cases) had higher stress levels, more severe childhood trauma, and a higher prevalence of females, alcohol consumption, and lower age compared to the non-suicide group (104 cases). Risk factors included lower age, poor interpersonal relationships, emotional abuse, and alcohol consumption.ConclusionThe study highlights the need to address stress factors and provide psychological support to safeguard adolescents’ mental health.